1992
DOI: 10.1071/ar9921353
|View full text |Cite
|
Sign up to set email alerts
|

Effects of abomasal protein and energy supply on wool growth in Merino sheep

Abstract: The relative importance for wool growth of energy-yielding nutrients compared with amino acids required for incorporation into wool proteins was assessed in an experiment in which most nutrients were supplied via the abomasum. Nine nutritional treatments, providing three levels of protein (53, 99 and 145 g/day) to the intestines at three levels of energy (5.2, 7.5 and 9.7 MJ/day), were given to 12 Merino sheep during three consecutive periods of 3 weeks in a balanced lattice design. Abomasal nutrients consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Similar positive response of wool growth to protein or purified amino acids supplementation was reported by Dove and Robards (1974) and Munro (1990 and1992). S-amino acids) for wool synthesis.…”
Section: Wool Growthsupporting
confidence: 85%
“…Similar positive response of wool growth to protein or purified amino acids supplementation was reported by Dove and Robards (1974) and Munro (1990 and1992). S-amino acids) for wool synthesis.…”
Section: Wool Growthsupporting
confidence: 85%
“…37 al. 1984 and by variation in pasture availability and hence ewe intake (Allden 1979;Sumner 1983;Reis et al 1992). In most situations these are confounded to a considerable degree because the short days of winter coincide with periods of low pasture availability and quality.…”
Section: Introductionmentioning
confidence: 99%
“…There is limited research which has investigated the effects of feeding distillers' grains to Merino sheep on wool production; however, numerous studies have observed improvements in wool traits in sheep fed dietary supplements with similar nutritive value to distillers' grains (Reis et al, 1992;Datta et al, 1999;White et al, 2000;Habib et al, 2001;Silva et al, 2007). It was difficult to determine in this study whether the improvements in wool growth 108 A. S. Graham et al…”
Section: Wool Performancementioning
confidence: 71%